Study of Orientation on The Effectiveness of Photovoltaic Shading Installation in The Ulil Albab Mosque, Yogyakarta - Hendrawati, Dyah; Setyowati, Erni; Prianto, Eddy; Dwiyanto, Agung (Journal of Architectural Research and Design Studies, 2024)
A mosque is a place of worship oriented towards the Qibla, which for the Yogyakarta area is in the northwest direction, or 294.7°. The Qibla will affect the orientation and possibly the shape of the building. The northwest direction of buildings in Yogyakarta has a relatively high solar factor value. The orientation of the building and the dominant shape of the building towards the Qibla cannot be avoided by architects because of the rule of shafts during congregational prayers. This research is expected to find the practical orientation and layout of photovoltaic installations that function as shading, which can reduce solar heat radiation. It is hoped that the distinctive orientation of the mosque will have great potential to produce maximum renewable energy by installing solar/photovoltaic panels. The orientation has excellent potential for a mosque building to produce maximum renewable energy by installing photovoltaic (PV) panels in addition to the roof. This research aims to clearly and measurably determine the potential for renewable energy in an existing mosque, namely the Ulil Albab Mosque, Yogyakarta. The method used in this research is to carry out simulations on all facade orientations using FormIt software to find the most effective potential facades for installing PV. This research shows the most significant potential for installing photovoltaics without disturbing the performance of other buildings and getting optimal energy on the side west by producing 86,76 kWh/year. Keywords: orientation; performance; PV; solar radiation